High non-specific binding of the β1-selective radioligand 2-125I-ICI-H - Riemann, B.; Law, M. P.; Kopka, K.; Wagner, St.; Luthra, S.; Pike, V. W.; Neumann, J.; Kirchhefer, U.; Schmitz, W.; Schober, O.; Schäfers, M. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: As results of cardiac biopsies suggest, myocardial β1-adrenoceptor density is reduced in patients with chronic heart failure. However, changes in cardiac β2-adrenoceptors vary. With suitable radiopharmaceuticals single photon emission computed tomography (SPECT) and positron emission tomography (PET) offer the opportunity to assess β-adrenoceptors non-invasively. Among the novel racemic analogues of the established β1-selective adrenoceptor antagonist ICI 89.406 the iodinated 2-I-ICI-H showed high affinity and selectivity to β1-adrenoceptors in murine ventricular membranes. The aim of this study was its evaluation as a putative sub-type selective β1-adrenergic radioligand in cardiac imaging. Methods: Competition studies in vitro and in vivo were used to investigate the kinetics of 2-I-ICI-H binding to cardiac β-adrenoceptors in mice and rats. In addition, the radiosynthesis of 2-125I-ICI-H from the silylated precursor 2-SiMe3-ICI-H was established. The specific activity was 80 GBq/µmol, the radiochemical yield ranged from 70 to 80%.Results: The unlabelled compound 2-I-ICI-H showed high β1-selectivity and -affinity in the in vitro competition studies. In vivo biodistribution studies apparently showed low affinity to cardiac β-adrenoceptors. The radiolabelled counterpart 2-125I-ICI-H showed a high degree of non-specific binding in vitro and no specific binding to cardiac β1-adrenoceptors in vivo. Conclusion: Because of its high non-specific binding 2-125I-ICI-H is no suitable radiotracer for imaging in vivo.
Keywords: SPECT; PET; β1-adrenoceptor radioligands; cardiac imaging